KEMAMPUAN NEGOSIASI ORGANISASI MAHASISWA DALAM PEREBUTAN POSISI PENYELENGGARA PEMILU DI KABUPATEN PANGANDARAN - Maulana, Acep Ridwan; Iqomah, Riksa (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
The focus of this study aims to analyze negotiation techniques carried out by student organizations in the fight for election organizer positions in Pangandaran Regency. This research uses qualitative methods with a participatory research approach, or commonly called Participatory Research Method on several student organizations involved in the fight for positions in elections in Pangandaran Regency. The results showed that there are several factors that influence the occurrence of conflict, such as differences in vision and mission, political competition, differences in strategic approaches, and differences in interests. This conflict dynamic can affect the existence of student organizations, but it can also be an opportunity for organizational growth and development.